2015
DOI: 10.1021/acs.jnatprod.5b00179
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Electrophilic Sesquiterpene Lactones fromVernonia amygdalina: New Members and Differences in Their Mechanism of Thiol Trapping and in Bioactivity

Abstract: In addition to known compounds, the leaves of Vernonia amygdalina afforded the new sesquiterpene lactones 14-O-methylvernolide (2), 3'-deoxyvernodalol (6), and vernomygdalin (8). These and related compounds were evaluated for modulation of a series of thiol trapping-sensitive transcription factors (NF-κB, STAT3, and Nrf2), involved in the maintenance of the chronic inflammatory condition typical of human degenerative diseases. Vernolide (1) emerged as a potent inhibitor of STAT3 and NF-κB and showed cytostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Biological activity of V. amygdalina species has been reported as antimicrobial 5 , antitumor 6,7 , anticancer 8,9 , anti-inflammatory 10 , and antidiabetic 11 . Extracts of the leaves of V. amygdalina contain flavonoid compounds, which are secondary metabolites to act as antioxidant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Biological activity of V. amygdalina species has been reported as antimicrobial 5 , antitumor 6,7 , anticancer 8,9 , anti-inflammatory 10 , and antidiabetic 11 . Extracts of the leaves of V. amygdalina contain flavonoid compounds, which are secondary metabolites to act as antioxidant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It has received considerable scientific interest due to the observation that adult chimpanzees with malaria returned to normal activity after chewing the extract of the bitter juice of this species [ 1 ]. Over the years, several studies on the chemical components of this species, including flavonoids [ 2 ], sesquiterpene lactones [ 3 ], steroidal saponins [ 4 , 5 , 6 ], and fatty acids [ 7 ], have been performed. Previous studies have indicated different bioactivities of this species, including anti-inflammation [ 8 ], anti-malaria [ 9 ], anti-obesity [ 10 , 11 ], antioxidant [ 12 , 13 ], anti-tumor [ 14 ], and other activities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective also includes the characterization of the as-synthesized nanoparticles. Both plants are known to be medicinal with various therapeutic benefits (Abay et al, 2015;Asante et al, 2016;Luo et al, 2011;Sinisi et al, 2016;Subarpriya, 2005). The synthesized silver nanoparticles were characterized by UV-Vis spectroscopy, FTIR and powder X-ray diffraction (PXRD).…”
mentioning
confidence: 99%